Práticas de Last Planner System como estratégia para melhorias em canteiros de obras: estudo de caso em uma obra vertical em Curitiba - PR - Bergamo, Bruna (2023)
The civil construction sector represents an important source of income for the Brazilian economy. However, the construction industry has stagnated with regard to developments, encountering difficulties in managing resources, as well as materials and labor, making the rate of waste, rework and activities that do not add value to production very high. In view of this, it was necessary to seek new philosophies and management trends in order to improve processes, aiming at greater competitiveness and rationalization of costs. In this way, in order to meet the needs of the market, it was possible to adapt Lean Construction to the sector, seeking to reduce waste and add value to the final product. Lean Construction is a philosophy that seeks to reduce the resources needed for the production of construction processes. The objective of this research is to present that with an elaborate planning and with actions and techniques guided by the Last Planner System, it is possible to obtain data that help in the continuous improvement of the construction site, maintaining the project deadline and eliminating the waste common to the sector. This work is justified by the possibility and opportunity to analyze that lean construction promotes the elimination of waste in construction, increasing productivity and gaining production rhythm through tools, optimizing deadlines without compromising quality. Thus, a case study was carried out to obtain the data that support the research. At the construction site under study, some basic Last Planner methodologies were already part of the employees’ routine, and it was through them that the engineering team observed the reduction in the productivity of the operation, só the researcher chose to initially conduct interviews with employees of the undertake in order to understand the reasons for non-compliance with activities protected in short-term meetings. With the obtaining of the interview answers, a data analysis was carried out and an action plan was implemented for the incentives of services with greater criticality in the production, through this it was possible to evaluate what could be done as an improvement. Through the results obtained and presented, it is possible to conclude that the Last Planner brings several improvements to the construction site as it allows the analysis of indicators in advance and the tools complete add value as they allow quick improvements for the implementation of action plans, minimizing future problems and delays in the schedule that impact on several pillars of a project.